Best Practices of Hospitals in Management of Epidemic Conditions: A Scoping Review: Practices of Hospitals in the Management of Epidemic Conditions - Tahmasebi, Ali; Masoudi asl, Iravan; Aryankhesal, Aidin; Vatankhah, Soudabeh; Masoumi, Gholamreza (Galen Medical Journal, 2023)
Background: Many hospitals globally have valuable experiences in preparing for man-agement and responding to infectious epidemics. Identifying and analyzing these expe-riences can provide comprehensive and practical data for decision-making and effec-tive performance. This study aimed to conduct a scoping review and content analysis of the best practices of hospital (private or public) management in epidemic conditions.Materials and Methods: This research is a scoping review and content analy-sis, conducted in 2021. Data was collected by searching different databases, includ-ing Pubmed, Scopus, Web of Sciences, ProQuest, websites, search engines, and pub-lic reports without time limits. Content analysis was performed for data analysis.Results: We retrieved 8842 records from databases and other sources. Finally, 24 studies from 12 countries were selected for analysis. Most studies belonged to the United States (9 cas-es), and most subjects were on Coronavirus disease 2019 (Covid-19) (19 studies). We clas-sified the results into two major categories of in-hospital executive readiness and logistic readiness. Executive readiness included 11 main categories (physical structure, resource man-agement, exposure reduction, patients and caregivers’ management, corpse management, dis-infection, staff support, patient admission, instructions and guidelines, tele- communication, and education) and 26 sub-categories. Logistic readiness consisted of three major categories (leadership/team making, communication, and using capabilities) and five sub-categories.Conclusion: Healthcare managers can use the identified categories and dimen-sions of managerial readiness and responsiveness as an action plan during an in-fectious disease epidemic.